Computed Tomography-Guided Percutaneous Gastrostomy/Jejunostomy for Feeding and Decompression - Albrecht, Heinz; Hagel, Alexander; Schlechtweg, Philipp; Förtsch, Thomas; Neurath, Markus; Mudter, Jonas (Nutrition in Clinical Practice, 2017)
An effective method for long-term enteral feeding or stomach decompression is the use of a percutaneous gastrostomy (PEG) or sometimes jejunostomy (PEJ). Under certain circumstances (eg, inadequate transillumination), endoscopic placement of PEG/PEJ tubes is impossible. In these cases, computed tomography (CT)-guided PEG/PEJ may represent an alternative technique. In this study, we evaluate indications, results, and complications of CT-guided PEG/PEJ.A total of 102 consecutive referred patients were enrolled in the study. Patients came to the endoscopy unit of our department to undergo a CT-guided PEG/PEJ for long-term intragastric/intrajejunal feeding (n = 57) or decompression (n = 45). The majority (n = 98) received a pull-through PEG/PEJ with simultaneous gastroscopy/jejunoscopy. Dose length product and the effective dose for every patient were calculated.PEG/PEJ tube placement was successful in 87.3% (89 of 102). Feeding PEG/PEJ tube placement was successfully completed in 91.2% (52 of 57); decompressive PEG/PEJ tube placement was likewise successfully completed in 82.2% (37 of 45). No procedure-related mortality was observed. Minor complications (eg, tube dysfunction, local bleeding, minimal leakage, local skin infection) were observed in 13 patients. The complication rate was similar between the feeding and decompression groups ( P = .9).CT-guided PEG/PEJ is a feasible and safe method with a low procedure-related morbidity rate for patients where endoscopic placement via transillumination is not successful. Thus, the procedure is an attractive alternative to surgical tube placement. Long-term complications, mainly tube disturbances, can be treated easily.
EVALuna2:14587

Molecular signature for lymphatic metastasis in colorectal carcinomas. - Croner, Roland S.; Förtsch, Thomas; Brueckl, Wolfgang M.; Roedel, Franz; Roedel, Claus; Papadopoulos, Thomas; Brabletz, Thomas; Kirchner, Thomas; Sachs, Martin; Behrens, Jürgen; Klein-Hitpass, Ludger; Stürzl, Michael; et al. (Annals of Surgery, 2008)
Fifty differently expressed genes between stage UICC I, II versus III CRC were identified respecting the selection criteria by allowing for multiple testing. The data validation by the independent clinical study confirmed our results. In comparison to MC, the genes were over- or underexpressed. They belong to various functional groups such as cellular adhesion, transporters, signaling, metabolism, protein synthesis, gene control, and immune system. Forty tumor samples of stage UICC I, II CRC, 40 samples of stage III CRC, and 25 biopsies of healthy mucosa (MC) were shock frozen in liquid nitrogen and underwent cryotomy after manual dissection for tumor tissue or MC enrichment. Isolated RNA was hybridized to GeneChips (HG-U133A, Affymetrix). Preprocessing of the microarray results was done by the robust multichip average method, and differentially expressed genes were selected by the maximum Wilcoxon statistic over 22,215 probe sets. The results were validated at an independent clinical study. Our large patient cohort and the data validation on an independent study identified 50 differentially expressed genes between CRC of different histopathologic stages. These findings indicate that molecular staging of CRC may be possible, which could help to guide individual CRC treatment before surgery. TNM-staging of colorectal carcinomas (CRC) relies on the histopathologic workup of the surgically removed specimen. If valid preoperative staging methods existed, patients could be selected for adequate individual therapy before surgery. Microarray techniques provide a promising tool to identify stage-specific molecular signatures on primary tumor biopsies. RESULTS MATERIAL AND METHODS CONCLUSION PURPOSE

Over-the-scope-clipping in colonic perforation caused small-bowel fixation and pneumoperitoneum requiring surgical repair - Albrecht, Heinz; Naegel, Andreas; Hagel, Alexander; Rösler, Wolf; Förtsch, Thomas; Neurath, Markus; Atreya, Raja; Raithel, Martin (Endoscopy, 2014)
EVALuna2:1835

Repeated cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with recurrent peritoneal carcinomatosis - Vassos, Nikolaos; Förtsch, Thomas; Aladashvili, Archil; Hohenberger, Werner; Croner, Roland S. (World Journal of Surgical Oncology, 2016)
Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) has become the treatment of choice for resectable peritoneal carcinomatosis (PC) and improved the survival of these patients. The situation changes if PC recurs and repeated CRS with HIPEC is considered. The patient selection and outcome of the repeated approach has not been well described. We analyzed our cohort and share the experiences.Ninety-three CRS/HIPEC procedures, performed in 85 patients during the period 2001-2013, were examined in a retrospective analysis. Type of primary, ECOG status, peritoneal cancer index (PCI), completeness of cytoreduction (CC), duration of hospitalization, postoperative morbidity, mortality, and disease-free/overall survival were reviewed.Six patients (7%) underwent a second CRS/HIPEC (median interval between the two procedures: 26 months, range 8-61) including two patients with mesotheliomas, one patient with ovarian adenocarcinoma, one patient with leiomyosarcoma of uterus, one patient with colon adenocarcinoma, and one patient with appendiceal adenocarcinoma. The last two patients underwent a third CRS/HIPEC, 25 and 36 months, after the second procedure. The median PCI was 14 (range, 4-26) during the first and 20 (range, 7-39) during the second CRS/HIPEC of these patients. Completeness of cytoreduction score of 0 (CC-0) was achieved in all first procedures and in 67% of second procedures (CC-0; n=4 and CC-1; n=2). A CC-0 score was possible in both of the third procedures. The mean operating time was 444 min (range, 198-642) and 427 min (range, 239-617) during the first and the second procedure. Median intensive care unit (ICU) was 2 days, and hospital stay after second CRS/HIPEC was 17 days (range, 7-50). The 30-day morbidity after repeated CRS/HIPEC was 33% (16% for grade III-IV complications), and there was no 30-day mortality neither after the second nor after the third CRS/HIPEC. Median disease-free interval between first CRS/HIPEC and peritoneal recurrence was 17 months (range, 8-30). Median disease-free survival of 18 months (range, 4-33) was achieved after the second CRS/HIPEC. After a median follow-up of 74 months (range, 39-151), all patients are alive with disease (n=5) or disease free (n=1) under chemotherapy.In experienced centers, repeated CRS/HIPEC can be performed with safety. Patient selection and correct timing is of particular importance in achieving control of the disease. Repeated CRS/HIPEC should be considered as treatment option for selected patients with recurrent PC.
EVALuna2:15226

Results of isolated limb perfusion for metastasized malignant melanoma - Schellerer, Vera; Frenger, Johannes; Merkel, Susanne; Göhl, Jonas; Kersting, Stephan; Grützmann, Robert; Erdmann, Michael; Förtsch, Thomas (Surgical Oncology-Oxford, 2021)
Background and objectives: Locoregional metastases are typical biological manifestations of advanced malignant melanomas. Treatment with hyperthermic isolated limb perfusion (HILP) should be considered in affected patients. In the present study, we have analyzed the results of HILPs performed in our department. Patients and methods: Eighty patients with locoregional metastases of the extremities received HILP at the Department of Surgery between January 2007 and December 2016. The mean follow-up was 38 months. Results: The study included 50 men and 30 women (mean age: 63 years). The median time between melanoma diagnosis and HILP was 25 months (range: 1–219 months). HILP was performed in curative (n = 45) and palliative (n = 35) intention. Seventy-five patients received a drug combination of melphalan/dactinomycin and five patients received a drug combination of melphalan/tumor necrosis factor-alpha. Remission rates were determined in 72 of 80 patients (90%) as follows: partial response n = 28, complete response n = 25, no response n = 19. Of the 25 patients with complete response, 13 patients developed a new tumor manifestation during follow-up (locoregional recurrences n = 4; distant metastases n = 3; both n = 6). The median overall survival rate was 33 months. Tumor stage influenced the survival rate significantly (p = 0.001). Patients with complete response showed a significantly better overall survival than patients with partial or no response (p = 0.016). Conclusion: HILP is an effective therapeutic option in patients with locoregional metastases. This procedure carries a certain risk of side effects and adverse events but overall results in good response rates. Therefore, HILP should be offered to selected patients based on an individual discussion, considering their health status and oncological prognosis.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Hyperthermic isolated limb perfusion; In-transit metastases; Malignant melanoma; Recurrence; Survival